Sarcopenic Obesity and the Pathogenesis of Exercise Intolerance in Heart Failure With Preserved Ejection Fraction - Upadhya, Bharathi (Curr Heart Fail Rep, 2015)
Heart failure with preserved ejection fraction (HFpEF) is the most common form of heart failure (HF) in older adults. The primary chronic symptom in patients with HFpEF, even when well compensated, is severe exercise intolerance. Cardiac and peripheral functions contribute equally to exercise intolerance in HFpEF, though the latter has been the focus of fewer studies. Of note, multiple studies with exercise training have shown that exercise intolerance can improve significantly in the absence of improvements in exercise cardiac output, indicating a role of peripheral, non-cardiac adaptations. In addition, clinical drug trials performed to date in HFpEF, all of which have focused on influencing cardiovascular function, have not been positive on primary clinical outcomes and most have not improved exercise capacity. Mounting evidence indicates that sarcopenic obesity, characterized by the coexistence of excess fat mass and decreased muscle mass, could contribute to the pathophysiology of exercise intolerance in older HFpEF patients and may provide avenues for novel treatments.